2017
DOI: 10.1002/aoc.3958
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation reactions catalysed by molybdenum(VI) complexes grafted on UiO‐66 metal–organic framework as an elegant nanoreactor

Abstract: A heterogeneous catalyst was synthesized by immobilizing Mo(CO) 3 in a UiO-66 metal-organic framework. The benzene ring of the organic linker in UiO-66 was modified via liquid-phase deposition of molybdenum hexacarbonyl, Mo(CO) 6 , as starting precursor to form the (arene)Mo(CO) 3 species inside the framework. The structure of this catalyst was characterized using X-ray diffraction, and chemical integrity was confirmed using Fourier transform infrared and diffuse reflectance UV-visible spectroscopic methods.Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Both PMo12@UiO-66 and PMo11Co@UiO-66 catalyze the epoxidation of cyclooctene, whereas a relatively higher catalytic activity was observed for the Co-substituted catalyst sample. Based on the calculated TOF values of various catalysts listed in Table 2, it is observed that the activity of PMo11Co@UiO-66 (TOF 19 h -1 at 334 K) is comparable to that of POM-based catalysts like Mo(CO)3-L@UiO-66 (TOF 19 h -1 at 353 K) reported in literature, but is lower than that of our previously reported PMo12@COF-300 (TOF 44 h -1 at 334 K) [40,46,47]. It should be mentioned that the reference catalyst PMo11Co/UiO-66-imp, prepared by the impregnation method, is also reasonably active for the epoxidation reaction (Fig.…”
Section: Catalytic Performance Of Pom@uio-66 Compositesmentioning
confidence: 48%
“…Both PMo12@UiO-66 and PMo11Co@UiO-66 catalyze the epoxidation of cyclooctene, whereas a relatively higher catalytic activity was observed for the Co-substituted catalyst sample. Based on the calculated TOF values of various catalysts listed in Table 2, it is observed that the activity of PMo11Co@UiO-66 (TOF 19 h -1 at 334 K) is comparable to that of POM-based catalysts like Mo(CO)3-L@UiO-66 (TOF 19 h -1 at 353 K) reported in literature, but is lower than that of our previously reported PMo12@COF-300 (TOF 44 h -1 at 334 K) [40,46,47]. It should be mentioned that the reference catalyst PMo11Co/UiO-66-imp, prepared by the impregnation method, is also reasonably active for the epoxidation reaction (Fig.…”
Section: Catalytic Performance Of Pom@uio-66 Compositesmentioning
confidence: 48%
“…An early example of matrix isolation in a MOF via linker binding involved PSMet of the arene rings of MOF-5 with organometallic Cr, Mo and W tricarbonyl complexes. [116][117][118] The choice of this chemistry alleviates the challenges of retaining free coordinating sites, as the arene rings are a ubiquitous presence in MOF linkers. The reaction between MOF-5 and [Cr(CO) 6 ] in dibutyl ether and THF at 140 C afforded quantitative formation of the corresponding h 6 -arene tricarbonyl complex.…”
Section: (B) Mof Linker Matrix Isolationmentioning
confidence: 99%
“…The influence of the solvent on the catalytic properties of CsPM@HP-UiO-66-2CH 3 was also evaluated. As shown in Table 5, the catalytic activity of CsPM@HP-UiO-66-2CH 3 is solvent-dependent, 38,52,53 decreasing in the order of tetrachloromethane > 1,2-dichloroethane > acetonitrile > ethanol > 1,4-dioxane. Thus, the low polar halohydrocarbon solvent is more favorable in this catalysis system.…”
Section: Resultsmentioning
confidence: 98%